Jigsaw Type Cooperative Learning On Student Learning Outcomes In Algae Classification Practicum - Utami, Nur Rizki (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2022)
Background: The purpose of this study was to obtain information about the effect of jigsaw cooperative learning on students' concept mastery in algae classification practicum. Methods: Quasi experiment with a non-randomized control group pretest-posttest research design with a control class using conventional learning. The research instruments include concept mastery test, questionnaire, and teacher interview. Data analysis was carried out using the Wilcoxon test, and the questionnaire was analyzed by calculating the percentage. Results: The results of the data gain analysis showed that there was a significant effect of the Jigsaw cooperative learning model on students' mastery of concepts. The results of the student questionnaire showed that the implementation of the Jigsaw cooperative learning model received a positive response from the teacher and students. Keywords : Cooperative Learning; Jigsaw; Concept Mastery; Algae Classification